A library of Rhodamine6G-based pH-sensitive fluorescent probes with versatile in vivo and in vitro applications. Issue 6 (5th May 2022) - Swanson, W. Benton; Durdan, Margaret; Eberle, Miranda; Woodbury, Seth; Mauser, Ava; Gregory, Jason; Zhang, Boya; Niemann, David; Herremans, Jacob; Ma, Peter X.; Lahann, Joerg; Weivoda, Megan; et al.
Abstract : Acidic pH is critical to the function of nearly every cell in the body. Based on Rhodamine 6G, we have developed a versatile molecular platform for non-invasive, real-time fluorescence imaging of acidic microenvironments based on Rhodamine 6G. Abstract : Acidic pH is critical to the function of the gastrointestinal system, bone-resorbing osteoclasts, and the endolysosomal compartment of nearly every cell in the body. Non-invasive, real-time fluorescence imaging of acidic microenvironments represents a powerful tool for understanding normal cellular biology, defining mechanisms of disease, and monitoring for therapeutic response. While commercially available pH-sensitive fluorescent probes exist, several limitations hinder their widespread use and potential for biologic application. To address this need, we developed a novel library of pH-sensitive probes based on the highly photostable and water-soluble fluorescent molecule, Rhodamine 6G. We demonstrate versatility in terms of both pH sensitivity ( i.e., p K a ) and chemical functionality, allowing conjugation to small molecules, proteins, nanoparticles, and regenerative biomaterial scaffold matrices. Furthermore, we show preserved pH-sensitive fluorescence following a variety of forms of covalent functionalization and demonstrate three potential applications, both in vitro and in vivo, for intracellular and extracellular pH sensing. Finally, we develop a computation approach for predicting the pH sensitivity of R6G derivatives, which could be used to expand our library and generate probes with novel properties.